The house of Wolves [compact disc, unabridged] - Patterson, James, 1947-; Lupica, Mike (Blackstone, 2023)
Joe Wolf applies a cutthroat determination to his life's work, from to building a California business empire to parenting three sons and a daughter. Kill or be killed. So when the patriarch takes a deadly cruise on San Francisco Bay, Joe Wolf's bloodline becomes SFPD's lifeline. Detective Ben Cantor trails the "pack of wolves" as the siblings vie for control of their legacy of power and assets. All four have the means and the motive to commit murder, but only one of them is most like Joe Wolf. Only one of them earned their father's love. Lurking in the shadows is the real .alpha wolf. That creature survives on instinct. And desire. To kill all the wolves dead.